Русские названия почек. Словообразовательная и семантическая реконструкция - Ушинскене, В. (Kalbotyra, 1992)
A group of anatomical terms denoting kidney in Russian and its dialects is being analysed in the paper. As the analysis shows this group of terms was formed at the epoch of dialectal development of Proto - Slawonic and at the time of independent formation of Slavonic languages. Most of the terms are polisemantic: the meaning ‘kindey’ is the single for only some words.The Russian terms proper are of secondary semantics. The established semantic pattern are being presented.